Tomatoes for Neela - Lakshmi, Padma; Martinez-Neal, Juana (New York : Viking Children's Books, 2021)
As Neela and her mother cook together, they find a way for Neela's grandmother, who lives in India, to share in both the love and the flavors of the day. Includes tomato facts.
Ages 3-7.
Grades K-1.
Keywords: Cooking -- Juvenile fiction; Tomatoes -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Grandmothers -- Juvenile fiction; East Indian Americans -- Juvenile fiction; Picture books